Biochar and mycorrhizal fungi in the cultivation of Anadenanthera colubrina (Vell.) seedlings - Cruz, Anny Bianca Santos; Almeida, Thieres Santos; Nascimento, Camilla Caroline Fontes; Fernandes, Milton Marques (Revista de Ciências Agroveterinárias, 2025)
The objective of the research was to analyze the development of Anadenanthera colubrina (Vell.) Brenan seedlings, inoculated with mycorrhizal fungi and different doses of sewage sludge biochar in a nursery. The experiment was done in a forest nursery, in a completely randomized design. The statistical differences between increasing dosages of sewage sludge biochar and mycorrhizal fungi were studied. The three-month growth and ecophysiological parameters of A. colubrina seedlings were determined, and the results submitted to analysis of variance and Tukey's test at 5% probability. The dosage of 10% of sewage sludge biochar without mycorrhizal fungi was the best formulation for the production of Anadenanthera colubrina seedlings. The use of higher sewage sludge biochar dosages increased the P content in the substrate, inhibiting the action of mycorrhizal fungi in favor of Anadenanthera colubrina seedlings for a better development of morphological and ecophysiological parameters. The inoculation of mycorrhizal fungi in seedlings of Anadenanthera colubrina along with higher doses of sewage sludge biochar, the high P content can cause the mycorrhizal fungi to have the role of parasites instead of mutualists, absorbing carbon from the plant, without compensating it, impairing the development of seedlings and ecophysiological performance.